METODOLOGÍA DE ANÁLISIS MULTICRITERIO ApLICACIÓN AL CRECIMIENTO SOSTENIbLE EN LA UNIÓN EUROpEA - Hermenegildo Chávez, Maria Victoria (2013)
This work have as main objective to show the methodology of PROMETHEE Multicriteria Analysis, performing a ranking of alternatives and between them we will choose the best, applying a set of criteria that are in conflict with each other. We will do a study of ranking of countries of Europe Union to find what country leads and moves towards to sustainable development (country that dominates at the other countries), and we will use computer tools powerfull in order to achieve this goal. The data have been obtained of EUROSTAT